Relationship Between Bitumen and Copper-Lead-Zinc Mineralization in the Mid-Silurian Carbonates in the Vicinity of Hamilton, Ontario - Cheung, Sha-Pak (My University, 1975)
Previous workers in the Hamilton area have pointed out the occurance of lead and zinc mineralization within the Mid-Silurian carbonate beds. They also mentioned the existance of bitumens in these rock units.
Analysis of 30 dolomite samples and separated bitumens by atomic absorption for Cu, Pb, Zn showed that the localization of the metals in the carbonates was controlled by the concentration of the bitumens in the rocks.
Analysis of 5 bitumens samples by atomic absorption for Cu, Pb, Zn suggested that the bitumens act merely as a reducing agent and are not preferred sites for base metal accumulation.
Keywords: Hamilton, lead, zinc, mineralization, Mid-Silurian, bitumen, carbonates